Going fast and getting lost : gene duplication in yeast - Scannell, Devin (Trinity College (Dublin, Ireland). Department of Genetics, 2007)
In this thesis I study how duplicate gene pairs created by a whole-genome duplication in an ancestor of several yeast species were resolved. I show that gene duplication may lead not just to the emergence of new gene functions, but also to the emergence of new species. I used comparative genomics between ten hemiascomycete yeasts to study both the process of gene loss that caused over 4000 genes to be rapidly lost from the S. cerevisiae genome and the altered molecular evolution of those genes that have been retained in duplicate. Among the genomes I studied was that of the non-model hemiascomycete yeast Kluyveromyces polysporus, which was sequenced, annotated and analyzed during the course of this thesis.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin